2016
DOI: 10.1007/s12663-016-0978-3
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Efficacy of C-Reactive Protein and Total Leucocyte Count as Markers for Monitoring the Course of Odontogenic Space Infections

Abstract: CRP displayed a more consistent relation with clinical severity of the infection than TLC. Hence it could be more reliably employed to judge the progress in a patient with OSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…This was contrary to the present study where all the patients had elevated levels of CRP as well as TLC but there was variation in ESR in few patients. 7 Bagul R et al and Seppänen L et al in their studies have observed that the levels of CRP and WBC count were increased in the first visit of the patient presenting with maxillofacial odontogenic infection but it subsequently decreased in the follow-up visits following surgical and medical management. They did not observe any superiority in CRP as compared to WBC count.…”
Section: Discussionmentioning
confidence: 95%
“…This was contrary to the present study where all the patients had elevated levels of CRP as well as TLC but there was variation in ESR in few patients. 7 Bagul R et al and Seppänen L et al in their studies have observed that the levels of CRP and WBC count were increased in the first visit of the patient presenting with maxillofacial odontogenic infection but it subsequently decreased in the follow-up visits following surgical and medical management. They did not observe any superiority in CRP as compared to WBC count.…”
Section: Discussionmentioning
confidence: 95%
“…23 Conversely, a recent study showed that CRP level has a more consistent relationship with the clinical severity of the infection than with the leucocyte count. 24 Sierra-Diaz et al 25 used a flow cytometry method to investigate the expression of TREM-1 in urine samples and to compare sTREM-1 levels between UTI and non-UTI samples. They detected TREM-1 expression in both the UTI and non-UTI group, but the levels were significantly higher in the UTI group.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography and ultrasound imaging are used in the diagnosis and surgical managementof severe spreading infections (20). In in-patient care of severe infections, clinical examination can be complemented with determination of leukocyte count and serum C-reactive protein (CRP) level (21).…”
Section: Diagnosis Of Acute Dental Infectionsmentioning
confidence: 99%